Protein folding does not prevent the nonclassical export of FGF1 and S100A13 - Graziani, Irene (2009)
Newly synthesized proteins are usually exported through the endoplasmic reticulum (ER) and Golgi due to the presence in their primary sequence of a hydrophobic signal peptide that is recognized by the ER translocation system. However, some secreted proteins lack a signal peptide and are exported independently of ER-Golgi. Fibroblast growth factor (FGF)1 is included in this group of polypeptides, as well as S100A13 that is a small calcium-binding protein critical for FGF1 export. Classically secreted proteins are transported into ER in their unfolded states. To determine the role of protein tertiary structure in FGF1 export through the cell membrane, we produced the chimeras of FGF1 and S100A13 with dihydrofolate reductase (DHFR). The specific DHFR inhibitor, aminopterin, prevents its unfolding. We found that aminopterin did not inhibit the release of FGF1:DHFR and S100A13:DHFR. Thus, FGF1 and S100A13 can be exported in folded conformation.